Dystocia caused by Sacrococcygeal Teratoma: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 23-year-old pregnant mother presented with labor pain for 14 hours with delivery of part of a baby with the exception of right leg. Single ultrasonography (USG) done at 34 weeks of gestation showed an anechoic area measuring 8 cm x 6 cm surrounded by a thin rim. The patient was put under general anesthesia (GA) and the right leg of the baby was drawn out of the uterus. A soft tissue mass partly cystic in nature, connected with the perineal region of the baby, prevented the complete delivery. After decompressing the mass, complete delivery was possible. But exploration of the uterus showed rupture in the left lateral wall. Laparotomy with repair of the uterus was done. Excision of the soft tissue mass of the baby was done one day after delivery and histology of the mass showed mature sacrococcygeal teratoma. Postoperative recovery of both the mother and the baby was good. DOI:10.3329/jbcps.v27i3.4296 J Bangladesh Coll Phys Surg 2009; 27: 169-172